Learning in higher education: strategies to overcome challenges faced by adult students – lessons drawn from two case studies in Portugal - Correia, Ana Maria R. (2010)
This paper appears in International Journal of Information and Communication Technology Education edited by Lawrence A. Tomei (Ed.) Copyright 2007, IGI Global, www.igi-global.com. Posted by permission of the publisher. URL:http://www.idea-group.com/journals/details.asp?id=4287.